The Plausibility of September–November Congo Basin Rainfall Change in Coupled Climate Models. Issue 11 (12th June 2019) - Creese, A.; Washington, R.; Munday, C.
Abstract: As one of three global hot spots of tropical convection, potential future changes to the Congo Basin climate system will have regional and tropics‐wide implications. However, the latest generation of climate models from the Coupled Model Intercomparison Project 5 disagree on the sign and magnitude of future change and diverge in their estimation of the historical rainfall climatology. This study assesses the plausibility of different signals of future rainfall change by examining the processes relating to rainfall projections in samples of historically wet or dry models during the September–November rainy season. In the west Congo Basin, there are no significant differences in rainfall change projections in models that are historically wet or dry. Both composites feature wetting in the north (up to 1.8 mm/day) and drying in the south, associated with enhanced tropical Atlantic sea surface temperatures, increased evaporation, and enhanced low‐level moisture flux into the basin. In the east Congo Basin, there is greater evidence that differences in model historical climatologies has an influence on the magnitude of future rainfall change. Historically wet models project significant wetting in the northeast (1.19 mm/day) associated with a weakened northern component of the African Easterly Jet (AEJ) and enhanced moisture convergence. Dry models do not capture the structure of the AEJs in the historical period, and so changes to the AEJs under warming do not produce the same wetting pattern. The analysis therefore casts doubt on the plausibility of the driest rainfall change signals in the east Congo Basin. Key Points: The magnitude and distribution of Congo Basin future rainfall change varies across coupled models Process‐based model evaluation can help to identify the plausibility of rainfall projections in the absence of observational data Historical model biases in the African Easterly Jets affect the magnitude of future rainfall change in the east Congo Basin